Laboratory Assessment for Filling Materials Used for Construction Kasha Chai Embankment /Kirkuk /Iraq - Khaled Ahmed Abdullad Alhadad; Hasnaa Salih Khalaf (Tikrit Journal of Pure Science)
Laboratory evaluation has been done , for raw data results of test and analysis for fine soil( filling materials) which it using in core construction dam, also to coarse soil (cover soil) for the same dam , according to International (American, British) & Iraqi  standers.